2020
DOI: 10.1177/0887403420916228
|View full text |Cite
|
Sign up to set email alerts
|

Building Holistic Defense: The Design and Evaluation of a Social Work Centric Model of Public Defense

Abstract: Holistic defense is a model of public defense rooted in the early 20th century recognition that lawyers and social workers should cooperate to advocate with and for individuals and communities in need. Prior work on holistic defense highlighted its potential to transform the lives of public defender clients by transforming the legal practice of attorneys. Comparatively, social workers’ roles in these transformations have been neglected. Yet many holistic defense programs begin by integrating social workers ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 53 publications
0
16
0
13
Order By: Relevance
“…One of the most substantial differences between this holistic model and traditional public defense is the emphasis of each respective model. With traditional defense, specifically public defense, the focus is case-centered engaging only a criminal defense attorney in providing a defense for the current criminal violation in the defense strategy (Harris, 2020;Lee et al, 2015). The traditional public defender is tasked with providing the defendant with legal representation for the specific charge(s) in that specific case without a focus on peripheral factors that may have led to the defendant being charged with a criminal violation.…”
Section: Traditional Public Defensementioning
confidence: 99%
“…One of the most substantial differences between this holistic model and traditional public defense is the emphasis of each respective model. With traditional defense, specifically public defense, the focus is case-centered engaging only a criminal defense attorney in providing a defense for the current criminal violation in the defense strategy (Harris, 2020;Lee et al, 2015). The traditional public defender is tasked with providing the defendant with legal representation for the specific charge(s) in that specific case without a focus on peripheral factors that may have led to the defendant being charged with a criminal violation.…”
Section: Traditional Public Defensementioning
confidence: 99%
“…Harris’s (2020) “Building Holistic Defense: The Design and Evaluation of a Social Work Centric Model of Public Defense” advances empirical analysis of holistic defense by evaluating a pilot program initiated by social workers in Santa Barbara, CA, for associations with reduced incarceration and recidivism. As Harris explains, holistic defense targets the underlying needs of defendants such as housing, employment, and mental health services that often correlate with poverty and involvement in criminal legal systems.…”
Section: System Interventions: Evaluating Programs and Identifying Opmentioning
confidence: 99%
“…Through an integration of social workers into its model, Tennessee's Knox County Public Defender's Office found that clients receiving social services were 3.8% less likely to be convicted of a misdemeanor and, when there were multiple charges, were convicted of 0.81 fewer misdemeanors as compared with clients who did not receive such services (Buchanan & Nooe, 2017; Buchanan & Orme, 2019). More recently, a pilot study of holistic defense in Santa Barbara, California, found that a greater proportion of holistic defense clients had their arraignment charges dismissed and pled guilty to a lower percentage of charges (Harris, 2020). On average, holistic defense resulted in 1500 fewer days of incarceration for clients as compared with controls (Harris, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a pilot study of holistic defense in Santa Barbara, California, found that a greater proportion of holistic defense clients had their arraignment charges dismissed and pled guilty to a lower percentage of charges (Harris, 2020). On average, holistic defense resulted in 1500 fewer days of incarceration for clients as compared with controls (Harris, 2020).…”
Section: Introductionmentioning
confidence: 99%